Distribution of invasive scud, Apocorophium lacustre (Vanhoffen, 1911) in the Illinois Waterway, USA: Do habitat and water quality variables influence spatial distribution and relative abundance? - Trent W. Henry; Brandon S. Harris; Bradley Smith; Reuben P. Keller; James T. Lamer (Aquatic Invasions, 2024)
Apocorophium lacustre – a species of benthic amphipod native to American and European estuaries along the North Atlantic Ocean – has rapidly expanded outside of its native range and is now established in the Illinois, Upper Mississippi, and Ohio river systems, USA. A. lacustre is considered high risk for colonization and disruption of the Laurentian Great Lakes’ benthic communities. To further our understanding of factors influencing A. lacustre distribution and its threat to the Great Lakes, zoobenthic and habitat data were collected from colonization samplers (i.e., rock bags) deployed at 370 sites along the Illinois Waterway. A. lacustre was found in the lower six pools of the Illinois Waterway and was the most abundant amphipod collected in those pools. Our results parallel other studies in that A. lacustre was not observed upstream of Dresden Island Pool, but A. lacustre was found ~11 km farther upstream of any previous records. Generalized linear mixed effects modeling indicated that parameters pertaining to food availability, water quality, and impoundment influenced A. lacustre abundance. Model averaging identified five statistically significant variables: A. lacustre abundance was negatively associated with turbidity, fluorescent dissolved organic matter, and vegetation density and positively associated with temperature and downstream distance (i.e., closer to the next downstream dam). Our findings of what factors influence A. lacustre abundance should be of broad interest to risk assessment and invasion forecasting in other regions where A. lacustre have been or may be introduced.